Perirectal Hematoma and Intra-Abdominal Bleeding after Stapled Hemorrhoidopexy and STARR—A Proposal for a Decision-Making Algorithm - Popivanov, Georgi (Medicina (Kaunas), 2020)
Background and Objectives: The present study aims to assess the effectiveness and current evidence of the treatment of perirectal bleeding after stapled haemorrhoidopexy. Materials and methods: A systematic literature review was performed that combined the published and the obtained original data after a search of PubMed, Web of Science, and SCOPUS. Results: The present systematic review includes 16 articles with 37 patients. Twelve papers report perirectal and six report intra-abdominal bleeding. Stapled hemorrhoidopexy (SH) was performed in 57% of cases (3 PPH 01 and 15 PPH 03), stapled transanal rectal resection (STARR) in 13%, and for 30% information was not available. The median age was 49 years (±11.43). The sign and symptoms of perirectal bleeding were abdominal pain (43%), pelvic discomfort without rectal bleeding (36%), urinary retention (14%), and external rectal bleeding (21%). The median time to bleeding was 1 day (±1.53 postoperative days), with median hemoglobin at diagnosis 8.8 ± 1.04 g/dL. Unstable hemodynamic was reported in 19%. Computed tomography scan (CT) was the first examination in 77%. Only two cases underwent the abdominal US, but subsequently, a CT scan was also conducted. Non-operative management was performed in 38% (n = 14) with selective arteriography and percutaneous angioembolization in two cases. A surgical treatment was performed in 23 cases—transabdominal surgery (3 colostomies, 1 Hartmann’ procedure, 1 low anterior resection of the rectum, 1 bilateral ligation of internal iliac artery and 1 ligation of vessels located at the rectal wall), transanal surgery (n = 13), a perineal incision in one, and CT-guided paracoccygeal drainage in one. Conclusions: Because of the rarity and lack of experience, no uniform tactic for the treatment of perirectal hematomas exists in the literature. We propose an algorithm similar to the approach in pelvic trauma, based on two main pillars—hemodynamic stability and the finding of contrast CT.